x-2-6x=4

Simple and best practice solution for x-2-6x=4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-2-6x=4 equation:


Simplifying
x + -2 + -6x = 4

Reorder the terms:
-2 + x + -6x = 4

Combine like terms: x + -6x = -5x
-2 + -5x = 4

Solving
-2 + -5x = 4

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -5x = 4 + 2

Combine like terms: -2 + 2 = 0
0 + -5x = 4 + 2
-5x = 4 + 2

Combine like terms: 4 + 2 = 6
-5x = 6

Divide each side by '-5'.
x = -1.2

Simplifying
x = -1.2

See similar equations:

| -[8z-(11z+9)]=9+(2z+3) | | 4m^3-10m^2= | | -2p-6(3-2p)=6(p-3)-16 | | 5x+10=-20fory | | 3x(x-2)+5(x-2)=0 | | 38x-38=38x-38 | | -8(4b+4)+(33b-9)=0 | | 5x+6(x-11)=5(x-12) | | -2=t-3s | | 62+(6x)+(6x+6)=180 | | 16s^2+72s+18=0 | | 12(-82x+26)=84(2x+62) | | 5/3x=56 | | x+5/3=56 | | 4c^2-36c=0 | | 9(3x+6)+(x+2)=11 | | 2n(8n+1)=0 | | 9x+90+y=180 | | x(-5x+2)=24 | | -3u-w=u+7w | | 4x+8+5x-7=180 | | 12+6x=42 | | 6=t+7s | | 6(t-3)+6t=4(3t+5)-12 | | 5x-9x+8=-2+6 | | -2+3x=12 | | -6z-6=-12z+12 | | 9x-6+6x-1+82=180 | | ((-2w^2)/(v^4))^3 | | 5(-2)-2x=20 | | 1/40*n=60 | | 8x^2+21x-28=0 |

Equations solver categories